Prognostic ability of new T1 descriptors in the tumour, node and metastasis classification of surgically treated non-small-cell lung cancer. (19th May 2018) - Takenaka, Tomoyoshi; Yamazaki, Koji; Miura, Naoko; Takeo, Sadanori
Abstract: OBJECTIVES: In the tumour, node and metastasis (TNM) classification (8th edition) of non-small-cell lung cancer, T (tumour size) is determined solely according to the size of the solid component determined using computed tomography (CT). However, it is unclear whether tumours of equal size but with differing solid and part-solid components should be similarly treated. Herein, we assessed the prognostic significance of the newly proposed T1 descriptors with respect to the size of the solid component. METHODS: We analysed overall survival (OS) and disease-free survival (DFS) between groups of patients ( n  = 255) with solid or part-solid tumours using propensity score matching. The new staging system was used for classification and comparison of survival. RESULTS: Chest CT detected 7 non-solid tumours, 123 part-solid tumours and 125 solid tumours. The 5-year OS and DFS rates differed significantly between the solid tumour (OS 71.2%; DFS 65.4%) and part-solid tumour (OS 83.2%; DFS 78.2%) groups. However, among 81 propensity score matching pairs (including those matched according to the size of the solid component), OS and DFS did not significantly differ between groups. The 5-year OS rates according to disease stage were as follows: cIA1 88.0%; cIA2 79.4% and cIA3 67.6%. CONCLUSIONS: Propensity score matching of solid tumour and part-solid tumour groups did not reveal a significant difference in survival as a function of the size of the solid component. A study of a larger cohort is required to validate this result.